The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1186/1471-2490-13-61
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous tibial nerve stimulation (PTNS) efficacy in the treatment of lower urinary tract dysfunctions: a systematic review

Abstract: BackgroundPercutaneous Tibial Nerve Stimulation (PTNS) has been proposed for the treatment of overactive bladder syndrome (OAB), non-obstructive urinary retention (NOUR), neurogenic bladder, paediatric voiding dysfunction and chronic pelvic pain/painful bladder syndrome (CPP/PBS). Despite a number of publications produced in the last ten years, the role of PTNS in urinary tract dysfunctions remains unclear. A systematic review of the papers on PTNS has been performed with the aim to better clarify potentialiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
101
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(111 citation statements)
references
References 47 publications
3
101
0
2
Order By: Relevance
“…14 Other alternatives include percutaneous tibial nerve stimulation and sacral nerve stimulation. 15,16 The BESIDE study (NCT01908829) demonstrated a significant benefit with 12 weeks' solifenacin 5 mg plus add-on mirabegron in incontinent OAB patients vs solifenacin 5 and 10 mg monotherapy in terms of improving daily incontinence, micturition frequency and urgency. Furthermore, the safety profile of the combination was similar to that of mirabegron or solifenacin monotherapy.…”
mentioning
confidence: 99%
“…14 Other alternatives include percutaneous tibial nerve stimulation and sacral nerve stimulation. 15,16 The BESIDE study (NCT01908829) demonstrated a significant benefit with 12 weeks' solifenacin 5 mg plus add-on mirabegron in incontinent OAB patients vs solifenacin 5 and 10 mg monotherapy in terms of improving daily incontinence, micturition frequency and urgency. Furthermore, the safety profile of the combination was similar to that of mirabegron or solifenacin monotherapy.…”
mentioning
confidence: 99%
“…In humans, TNS has also become a very promising noninvasive (transcutaneous TNS) or minimally invasive (percutaneous TNS) therapeutic option for refractory lower urinary tract dysfunction. Percutaneous TNS was found to be effective in 37-100% of patients with idiopathic overactive bladder, in 41-100% of those with nonobstructive E U R O P E A N U R O L O G Y X X X ( 2 0 1 5 ) X X X -X X X urinary retention, and in upon 100% of patients with chronic pelvic pain syndrome, children with overactive bladder or dysfunctional voiding, and in patients with NLUTD [7]. In addition, TNS might improve fecal incontinence [33], highlighting the potential in the neurological patient often with both lower urinary tract and bowel dysfunction, although there is no high level of evidence study assessing the combined dysfunction.…”
Section: Findings In the Context Of Existing Evidencementioning
confidence: 96%
“…Tibial nerve stimulation (TNS), introduced by Stoller in the late 1990s [6], is a promising therapy for nonneurogenic lower urinary tract dysfunction [7]. The tibial nerve is stimulated by an electrode inserted 4-5 cm cephalad to the medial malleolus.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are no specific data in older population, two recent systematic reviews have shown success rates between 37% and 100% in nonresponders to first-line therapy of OAB, with no major complications reported. 88,89 Only temporal effects such as mild-moderate pain in the site of the puncture, bleeding at insertion site, leg cramp, or numbness/pain at the sole of the foot have been reported in about 8.5% of treated patients. Establishing whether these promising results can be expected in the older population is a matter of study.…”
Section: Neuromodulationmentioning
confidence: 99%